The Utilization of Areca Skin Fiber - Pumice and Epoxy Resin Towards The Characterization of Concrete Polymer - hakim, lukman (Talenta Publisher, 2019)
The manufacturing and characterization of polymer concrete made from the mixture of areca fiber, pumice and sand as an aggregate and epoxy resin as a binder material has been conducted. The mixture of sand, pumice and areca shell fiber varies with (50:50:0) g, (49:49:2) g, (48:48:4) g, (47:47:6) g, (46:46:8) g, (45:45:10) g respectively, and epoxy resin (25.30) g in every variation of aggregate (sand + pumice + areca fiber). The results reveal that the best mixture composition in accordance to the experiment was a mixture of sand and areca shell with a ratio of 48:48:2 g as well as the addition of 30 g epoxy resin. The physical properties of polymer concrete were analyzed. The density was 1.81 (g.cmË‰Â³) and porosity was 1%. Moreover, the mechanical properties were also analyzed by performing the impact test with the result of 7.5 KJ/mÂ² and bending strength test was 16.94 MPa. The XRD analysis indicated the presence of quartz, pumice stone, quartz, pumice stone hexagonal, while the areca fiber has an amorphous crystal shape.